Copeptin levels and blood lipid profile in borderline patients with or without self-mutilation - Korkmaz, Sevda; Ustundag, Bilal; Ozer, Omer; Tasc, Gulay; Kaya, Suheda; Atescelik, Metin; Atmaca, Murad (Aosis, 2016)
Purpose: Self-mutilation, known as self-harming behaviour of an individual without the intention of suicide, is commonly observed in individuals with borderline personality disorder. The objective of this study is to compare copeptin levels that are known to be related to aggressive behaviour and blood lipid profiles in borderline patients with and without self-mutilation. Methods: Twenty patients with self-mutilation [SM(+)] and 20 patients without self-mutilation [ SM(-)] between the ages of 18 and 49, diagnosed with borderline personality disorder based on DSM-IV-TR(8) diagnostic criteria and attended to by Firat University Psychiatry Polyclinic, participated in the study. Socio-demographic and clinical data form, Hamilton Depression Rating Scale, Hamilton Anxiety Rating Scale (HAMA) and Barrat Impulsivity Scale (BIS) were applied to all participants. Copeptin levels and plasma lipid levels were studied in the blood samples taken from the participants. Results: Mean copeptin level found in SM(+) group ( 37.54 +/- 18.8 ng/ mL) was statistically significantly higher than SM(-) group (18.53 +/- 16.6 ng/ mL) (p = 0.002). A negative correlation was found between mean copeptin and mean total cholesterol levels (r = -0.436; p = 0.005), and between copeptin and low-density lipoprotein cholesterol (LDL) levels (r = -0.403; p = 0.01) in both SM(+) and SM(-) patient groups. HAMA mean score for SM(+) group was found as 36.45 +/- 13.2, and for SM(-) group, it was found as 35.7 +/- 12.9. There was a statistically significant difference between the depression points achieved by the two groups (p = 0.046). BIS total points average for SM(+) group was determined as 71 +/- 9.71, whereas it was determined as 66.8 +/- 7.92 in SM(-) group. There was no statistically significant difference between the groups based on anxiety points. Barrat planning, Barrat motor and Barrat attention points for SM(+) group were higher than the SM(-) group. However, the difference was not statistically significant (p > 0.05). Conclusion: Findings of the study demonstrated that as cholesterol and LDL levels decreased, copeptin levels increased, and that could be related to the self- mutilation behaviour.
Keywords: Serum-Cholesterol; Suicidal-Behavior; Disorder; History